Results and Comparison of Volatility Between Prices Between IHSG and ISSI: A Case Study of the Turmoil Period 2020-2021 - Arie Sulistyawan; Wakhibah Dwi Khusnah; Kholid Murtadlo (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
Knowing the results and comparing the effect of the period of turmoil between the volatility of the Composite Stock Price Index(IHSG) and the Indonesian Sharia Stock Index (ISSI) is the purpose of this study. Then to compare the effect of the volatility of the IHSG and ISSI and find out the results of macroeconomic variables that show a period of turmoil in 2020 to 2021.The Covid-19 pandemic, the trade war between the United States and China, demonstrations against the Draft Law. Job Creation with Gross Domestic Product (GDP), interest rates, world oil prices, inflation, rupiah-dollar exchange rates, interest rates, world oil prices, Shanghai Stock Exchange (SSE) Composite Index, and New York. The Stock Exchange (NYSE) is a time of turmoil in this research. Five working days data from 2020 to 2021 which is used as a variable. Quantitative analysis uses TGARCH Model and VECM in this analysis method. Against the times of turmoil, Based on the results of TGARCH shows that ISSI volatility has a significant effect smaller.Compared to volatility IHSG, According to the results of VECM analysisshows that the period of turmoil from 2020 to 2021 has more of an impact on ISSI's volatility. ________________________________________ Tujuan dari penelitian ini adalah untuk mengetahui hasil dan membandingkan efek periode ketidakstabilan antara volatilitas Indeks Harga Saham Gabungan (IHSG) dan Indeks Saham Syariah Indonesia (ISSI). Selanjutnya, untuk membandingkan efek volatilitas IHSG dan ISSI serta mencari hasil dari variabel makroekonomi yang menunjukkan periode ketidakstabilan pada tahun 2020 hingga 2021. Pandemi Covid-19, perang perdagangan antara Amerika Serikat dan China, demonstrasi menentang Rancangan Undang-Undang Cipta Kerja dengan Produk Domestik Bruto (PDB), tingkat suku bunga, harga minyak dunia, inflasi, nilai tukar rupiah-dollar, tingkat suku bunga, harga minyak dunia, Indeks Komposit Bursa Saham Shanghai (SSE), dan Bursa Saham New York (NYSE) adalah periode ketidakstabilan dalam penelitian ini. Lima hari kerja data dari tahun 2020 hingga 2021 digunakan sebagai variabel. Analisis kuantitatif menggunakan Model TGARCH dan VECM dalam metode analisis ini. Terhadap periode ketidakstabilan, berdasarkan hasil TGARCH menunjukkan bahwa volatilitas ISSI memiliki efek signifikan yang lebih kecil dibandingkan dengan volatilitas IHSG. Menurut hasil analisis VECM menunjukkan bahwa periode ketidakstabilan dari tahun 2020 hingga 2021 memiliki lebih banyak dampak pada volatilitas ISSI.